Selected Works from the Collection of Asher B. Edelman. (Zürich : Thomas Ammann Fine Art, 1987)
Picasso, Pablo ; Miro, Joan ; De Kooning, Willem ; Corky, Arshile ; Rauschenberg, Robert ; Warhol, andy ; Twombly, Cy ; Johns, Jasper ; Stella, Frank
Selected Works from the Collection of Asher B. Edelman / Ausgewählte Werke aus der Sammlung von Asher B. Edelman, Thomas Ammann Fine Art, Zürich, 17. Juni - 18. September 1987
Duits & Engels
kunstcatalogus